Original articleAdvanced reactive astrogliosis associated with hemangioblastoma versus astroglial-vascular neoplasm (“angioglioma”) - Matyja, Ewa; Grajkowska, Wiesława; Taraszewska, Anna; Marchel, Michał; Bojarski, Piotr; Nauman, Paweł (Folia Neuropathologica, 2007)
Hemangioblastomas of the central nervous system are often accompanied by a cyst exhibiting an extensive astroglial reaction. The cyst’s wall might be composed of various astroglial elements including reactive pilocytic or gemistocytic and hypertrophic astrocytes. The small tissue samples composed of compact gliotic tissue are sometimes nonrepresentative for primary hemangioblastoma tumour and might be confused with both pilocytic and diffuse infiltrative astrocytoma. Moreover, vascular anomalies of hemangioblastoma-like pattern could be combined with true neoplastic glial proliferation. Such association of glioma with certain types of vascular anomalies has been designated as angioglioma. In the current study we evaluated a series of hemangioblastomas accompanied by advanced astrogliosis of adjacent brain tissue. In some cases the histopathological features of pilocytic gliosis with numerous Rosenthal fibres and eosinophilic granular bodies strongly suggest the diagnosis of pilocytic astrocytoma. One tumour was identified as an angioglioma exhibiting a combination of hemangioblastoma-like tissue and pilocytic astrocytoma. The recognition of such an entity is important in differential tumour diagnosis and prognosis.